Uma luz na escuridão: ficção, memórias e (auto)biografia na escrita de Salim Miguel - Silva, Ana Cláudia de Oliveira da (2011)
Nur na escuridão (1999) tells the story of a Lebanese family that decides to leave their homeland and emigrate to the Americas, in order to find better living conditions. The crossing from this family between distinct worlds, as the East and West are, is constituted as indelible mark in the way of being and feeling from the characters and the narrator himself. In this scenario, crossing between worlds, cultures and traditions, it is inscribed the Salim Miguel s narrative, and their own life experience as an Arab immigrant. From these initial considerations, this dissertation sought to verify the role of narrator and his relationship with the memoirist discourse, as well as to examine, in the work, the interrelation of different literary genres such as (auto)biography, memories, biography and fiction itself.